(3GdJNWjW h GdJShjb GdSjGMj HGSJNOGe (BGIS /s - (3HXGXh, GHQGgjes ((3YeGf(B: s (3OGQ GdhQGb ddfTQ hGdJhRjY(B, s, 2009)
(3NUGFU h CfeGW UfGYI GdSjGMI, GdebheGJ GdLZQGajI ddehGbY GdSjGMjI, JMdjd CfeGW h GLGgGJ GdMQcI GdSjGMjI, GSJQGJjLjI h eQGMd JNWjW JNWjW GdehGbY GdSjGMjI , GdJcGed Hjf GdGbdje GdJNWjWj h GdGbdje GdSjGMj , Jbjje NWW JfejI GdehGbY GdSjGMjI, JWHjbGJ fXGe GdeYdheGJ GdLZQGaj aj GdJNWjW GdSjGMj, GdfeGPL GdJWhjQjI ddehGbY GdSjGMjI, eYGjjQ JUfja GdehGbY GdSjGMjI MSH OQLGJ JWhQgG h eYhbGJ JWhjQ GdehGbY GdSjGMjI, eJWdHGJgG h eHGOFgG, eaghe GdJShjb GdSjGMj h GdYhGed GdeDKQI aj, GdaQb Hjf GdhSGFd GdJbdjOjI h GdhSGFd GdeYJOeI Ydi GSJNOGe fXGe GdeYdheGJ GdLZQGaj aj JShjb GdehGbY GdSjGMjI, CSGdjH GdJShjb GdeJHYI MGdjG aj GdGQOf, JWHjbGJ fXGe GdeYdheGJ GdLZQGaj aj GdJShjb GdSjGMj, ebJQMGJ dJWHjb fXGe GdeYdheGJ GdLZQGaj aj JShjb GdehGbY GdSjGMjI aj GdCQOfs
Keywords: (3GdJNWjWs; (3GdJShjbs; (3GdSjGMI(B- (3GbJUGOjGJs